The Effect of Innovation and Foreign Ownership on ESG Disclosure - Noraida Hafni; Makaryanawati Makaryanawati; Endang Sri Andayani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to determine the effect of innovation and foreign ownership on ESG (Environmental, Social, and Governance) disclosure in companies indexed in the ESG Sector Leaders. This study uses secondary data sourced from company annual reports and sustainability reports for the period 2022-2024. Data processing uses panel data regression methods with EViews 13 software. Data collection was conducted using content analysis techniques. ESG disclosure refers to the 2021 GRI (Global Reporting Initiative) standard guidelines. This study produced a data sample of 99 observations for the 2022-2024 period. The novelty of this study involves control variables that are indicated to have an influence on ESG disclosure outside the selected independent variables. These control variables serve as proxies to capture company heterogeneity that may affect ESG disclosure. The findings reveal that innovation and foreign ownership do not have a proven effect on ESG disclosure in companies indexed as ESG Sector Leaders. The control variable of company age has an effect on ESG disclosure, while the control variables of company size and leverage do not affect ESG disclosure.